INFRACȚIUNI CONTRA PERSOANEI - PROVOCARE ÎN ADRESA SECURITĂȚII UMANE - Proca, Maria; Botnariuc, Victor (Institutul naţional de informaţii şi securitate „Bogdan, întemeietorul Moldovei”, 2022)
Today, in the literature, distinct attention is paid to human security as a component of national and international security. Human security is seriously threatened by crime, because crime has a strong negative and destabilizing impact on all spheres of a person's life. In this article the authors set out to analyze the impact of crimes against the person on human security. Also were analyzed qualitative changes in crimes against the person.
Keywords: securitatea umană